Profile and Outcome of Diabetic Admissions: A Retrospective Study from Eastern Nepal - Subedi, M.; Tripathi, P.M.; Pradhan, B.; Diwedi, S.; Bogati, S.; Subedi, S.; Maskey, R. (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Introduction: Despite the increasing prevalence of diabetes, lack of awareness about the disease, its consequences and lack of quality care in diabetes lead to delayed presentation to health care giver that might be associated with more number of complication and co-morbid condition of the disease which may adversely affect the outcome of the patient. Therefore we undertook this study to determine the common symptoms that lead to admission of patients suffering from diabetes along with the complications they present and their outcome. Methods: We analyzed data from the medical records available among admitted patients with diabetes over a period of 6 months. Results: Among 200 subjects with mean age of 52 years, majority had Type 2 diabetes mellitus, 53% were males and more than half had some other comorbidities. Most of them, 68% had microvascular complications, and 27% of them had some form of macrovascular complications. Conclusions: Despite of continuous effort from various organizations, micro and macrovacular complications are very high among diabetic patients, so more emphasis has to be given on prevention of these complications at various level of health care delivery system. Jour of Diab and Endo Assoc of Nepal 2018; 2 (1): 4-8